Challenges and perspectives of teaching in higher education in Nursing: a literary essay (Research, Society and Development, 2020)
Teaching can be considered as the exercise of teaching, which articulates the teaching and learning processes, activities that characterize or make the teacher. In turn, teaching in higher education is understood as a highly complex activity, as it is not restricted to doing in the classroom, since it articulates teaching, research and extension. This is a literature search with a qualitative approach, with the objective of describing challenges and perspectives of teaching in higher education in nursing. After an association of all the descriptors, 453 articles were found, 441 were excluded and selected 12. After the emerging reflective reading, two categories: teaching challenges in higher education in nursing and the perspective of teaching in higher education in nursing. The nurse's teaching practice must contain specific domains that guarantee a performance capable of contributing to the training of future nurses. Mastery of scientific knowledge and ability to transmit, in a productive and clear way, all content to their students, are pointed out as a necessary basis for good learning. Other related domains or field of professional experience in health services, holding ethical, moral and philosophical knowledge. It concluded whether the investment in pedagogy of higher education teachers in nursing, with the new information and communication technologies, is important and requires them to be able to create an environment conducive to learning, in which the teacher is the mediator of the construction of the saber, and I am not a mere transmitter.